Computational Study on Structural and Thermal Behavior of Aircraft Disk Brake Rotor for Different Materials - Joshi, Sachin; Poudel, Laxman; Dhakal, Samiksha (Journal of Advanced College of Engineering and Management, 2023)
Brakes are one of the most significant safety systems in an aircraft. The rotor will be exposed to large stresses which result in surface cracking, overheating of brake fluid, seals and other components during the braking process. Thus, one of the main tasks for the design of braking system is to reduce the stress, deformation and surface temperature of the brake rotor. This can be achieved by choosing the right material which will undergo the least thermal stresses. In this research a detailed study of structural and thermal analysis is carried out for disc brake rotor of DHC-6 Twin Otter with different materials. The objective of this research is to provide an efficient material for disc brake rotor which can dissipate heat generated during braking at faster rate and also being structurally safe. The materials chosen for the study are Mild Steel, Grey cast iron, Stainless steel, Cabon-carbon composite and Aluminum silicon carbide MMC. From the structural and thermal analysis it was found that the aluminum silicon carbide MMC disc brake rotor exhibits the superior performance against other materials with a mass of 2.37 Kg, deformation of 0.043617 mm, maximum stress of 167.91 MPa, maximum temperature of 250.85 oC and heat flux of 5.2043 W/mm2. The mass, stress, deformation and temperature developed in the aluminum silicon carbide MMC rotor is less than the original stainless steel rotor by 61.3%, 3.66%, 6.9% and 35.6% respectively. Similarly, the aluminum silicon carbide MMC rotor provides better heat dissipation as compared to original rotor due to an increment in heat flux by 15.26%.